40th Winter School on Wave and Quantum Acoustics Szczyrk, Poland, February 27 – March 4, 2011 - BUKOWSKI, Roman (Archives of Acoustics, 2011)
I have a great pleasure to inform the “AA” Readers that the 40th Winter Schoolon Wave and Quantum Acoustics, organized by Upper Silesian Division of the PolishAcoustical Society and Institute of Physics – Scientific-Didactics Center at Silesian Universityof Technology, is planned at the turn of February and March 2011 in beautifulscenery of Silesian Beskidy Mountains. Many times it was organized in Wisła, Skoczów,Szczyrk and Korbielów, and this year it will be organized again in Szczyrk.As always, the School has been a place where achievements of various sections ofphysical acoustics (especially molecular acoustics, quantum acoustics, acousto-optics,magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc.) are beingexchanged. Moreover, some similar and related topics, for example optoelectronics andthermal wave methods, will be presented too.As at the previous years, the School will be divided into three different, but complementary,parts – Winter Workshops (WW). Chronologically it will be: 7th WW onAcoustoelectronics (chairman Prof. Marian Urbanczyk, Silesian University of Technology,Gliwice), 7th WW on Molecular Acoustics, Relaxation and Calorimetric Methods(chairwoman Dr. Marzena Dzida, Silesian University, Katowice) and 16th WW on Photoacousticsand Thermal Waves Methods (chairman Prof. Jerzy Bodzenta, Silesian Universityof Technology, Gliwice). Moreover, this year we propose to participate in associatedconference – the 5th Conference on Integrated Optics – Sensors, Sensing Structuresand Methods (chairman Prof. Tadeusz Pustelny, Silesian University of Technology, Gliwice).